PERILAKU REMAJA TERHADAP PENGGUNAAN ORTODONTI CEKAT PADA SISWA SMA DON BOSCO PADANG - Addientya Maykeza; Rizanda Machmud; Lendrawati Lendrawati (Andalas Dental Journal, 2014)
Nowadays, the shifting of fixed orthodontic function becomes a lifestyle is more popular than before. The study is purpose to determine a relationship between teenager behaviour (knowledge, attitudes, and action) to fixed orthodontic appliance.This study using cross sectional study design. The sample was a high school students of Don Bosco Padang, Sumatera Barat. The number of samples are 90 people, that chosen by proportionate stratified random sampling technique. The data was collected by using a questionnaire to measure the level of knowledge, attitude and action. Data analysis using Chi-Square test. The result showed there was no significant relationship between teenager knowledge, attitude, and action with fixed orthodontic application in high school students of Don Bosco Padang. The conclusion from this study is that most of high school students of Don Bosco Padang have a high knowledge, positive attitude, and good action about fixed orthodontic treatment